Wind energy modeling and simulation. Volume 2, - Veers, Paul S. (Institution of Engineering and Technology, 2020)
The book consists of 9 chapters and covers the following topics: aerodynamics; wind turbine aero-servo-elasticity; rotor design; drivetrain analysis; offshore turbines; wind turbine control; systems engineering; wind plant electrical systems and grid modeling.
Keywords: Wind power -- Computer simulation.; Wind power plants -- Computer simulation.; elektronické knihy; electronic books